Optimization hydrogen production over visible light-driven titania-supported bimetallic photocatalyst from water photosplitting in tandem photoelectrochemical cell - Bashiri, R. (Elsevier Ltd, 2016)
Solar hydrogen production was investigated over a Cu-Ni doped TiO2 photocatalyst from water photosplitting in a tandem photoelectrochemical cell, which was made up by connecting a modified photoelectrochemical cell to dye solar cell in a series. A mathematical representation for preparation parameters for hydrogen production was successfully generated. Optimization of hydrogen production was conducted with varying preparation parameters of Cu-Ni doped TiO2 photocatalyst including molar ratios of water, acetic acid and Cu to titanium tetraisopropoxide. The optimum preparation parameters of photocatalyst was obtained at molar ratios of water, acetic acid and Cu to titanium tetraisopropoxide of 32, 4.9, and 5.9, respectively. Physical and photoelectrochemical characterization revealed that low content of water and Cu decreased the charge transfer resistance and charge carrier recombination rate on Cu-Ni/TiO2 surface. This is attributed to the better crystallinity and less degree of agglomeration which led to obtain optimum particle size at this condition. Maximum hydrogen production rate of 2.12Â mL/cm2. h was achieved under the optimum condition using the tandem photoelectrochemical cell in the aqueous KOH and glycerol solution under visible light irradiation (Î»Â >Â 400Â nm). Â© 2016 Elsevier Ltd